2022
DOI: 10.3390/biomedicines10092240
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 Variants Are Associated with the Risk for COPD and NSCLC Development, Better Overall Survival of the NSCLC Patients and Increased Chemosensitivity in the H1299 Cell Line

Abstract: Chronic obstructive pulmonary disease (COPD) is considered as the strongest independent risk factor for lung cancer (LC) development, suggesting an overlapping genetic background in both diseases. A common feature of both diseases is aberrant immunity in respiratory epithelia that is mainly regulated by Toll-like receptors (TLRs), key regulators of innate immunity. The function of the flagellin-sensing TLR5 in airway epithelia and pathophysiology of COPD and LC has remained elusive. We performed case–control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…In recent years, investigations exploring TLRs' expression and functional significance in NSCLC have intensified. These studies have reported diverse TLR expression patterns across different NSCLC subtypes, prompting the question of whether TLRs could serve as valuable biomarkers for this heterogeneous disease [22][23][24][25]. Understanding the potential of TLR expression as an independent prognostic biomarker is crucial, as it could contribute to refining risk stratification and guiding personalized treatment approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, investigations exploring TLRs' expression and functional significance in NSCLC have intensified. These studies have reported diverse TLR expression patterns across different NSCLC subtypes, prompting the question of whether TLRs could serve as valuable biomarkers for this heterogeneous disease [22][23][24][25]. Understanding the potential of TLR expression as an independent prognostic biomarker is crucial, as it could contribute to refining risk stratification and guiding personalized treatment approaches.…”
Section: Introductionmentioning
confidence: 99%